1997
DOI: 10.1002/(sici)1097-4644(1997)28/29+<166::aid-jcb20>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Oltipraz chemoprevention trial in Qidong, Jiangsu Province, People's Republic of China

Abstract: Oltipraz has been used clinically in many regions of the world as an antischistosomal agent and is an effective inhibitor of aflatoxin hepatocarcinogenesis in rats. This chemopreventive action of oltipraz results primarily from an altered balance in aflatoxin metabolic activation and detoxication. In 1995, a randomized, placebo-controlled, double-blind intervention was conducted in residents of Qidong, People's Republic of China, who are at high risk for exposure to aflatoxin and development of hepatocellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Thus both the formation of the reactive aflatoxin-epoxide and its detoxification are enhanced by oltipraz. Oltipraz was subsequently successfully used in a clinical trial in China during 1995 to demonstrate proof of principle in populations naturally exposed through diet [165]. The study had three groups (control, low dose intervention, and high dose intervention) and included an intervention period (8 weeks) and a clear-out period (8 weeks).…”
Section: Potential Intervention Strategiesmentioning
confidence: 99%
“…Thus both the formation of the reactive aflatoxin-epoxide and its detoxification are enhanced by oltipraz. Oltipraz was subsequently successfully used in a clinical trial in China during 1995 to demonstrate proof of principle in populations naturally exposed through diet [165]. The study had three groups (control, low dose intervention, and high dose intervention) and included an intervention period (8 weeks) and a clear-out period (8 weeks).…”
Section: Potential Intervention Strategiesmentioning
confidence: 99%
“…Oltipraz is a potent inducer of metabolic phase II enzyme glutathione S -transferase (GST) and also a competitive inhibitor of P450 1A2 and 3A4 enzymes , . Although oltipraz showed excellent results against AFB1-induced cytotoxicity in animal studies, adverse effects were reported in patients . The chemoprotection with dietary supplement chlorophyllin is achieved through the formation of complexes with AFB1 to reduce its bioavailability .…”
Section: Introductionmentioning
confidence: 99%
“…The potent cytotoxicity of AFB1 is attributed to the covalent DNA modification by the exo -epoxide metabolite ( , ), resulting in liver damage and possibly hepatocellular carcinoma ( 4−8 ) . In past decades, several effective chemoprevention agents, including oltipraz and chlorophyllins, have been developed and showed promising results in clinical trials ( ). Unfortunately, adverse effects were the major concern for oltipraz ( , ), whereas more mechanistic studies are required for chlorophyllins ().…”
Section: Introductionmentioning
confidence: 99%
“…In past decades, several effective chemoprevention agents, including oltipraz and chlorophyllins, have been developed and showed promising results in clinical trials ( ). Unfortunately, adverse effects were the major concern for oltipraz ( , ), whereas more mechanistic studies are required for chlorophyllins (). Recently, the screening of natural products, such as extracts from algae (), onion bulbs (), and kola seeds (), has identified several alternatives as potential candidates against AFB1.…”
Section: Introductionmentioning
confidence: 99%